MLH1 c.199G>A, a Known Mutation for Lynch Syndrome, Is Also Associated with Sebaceous Neoplasm - Wei-Sheng Li; Yan Li; Nai-Hui Zhou; Jing-Liu Liu; Zi-Liang Yang; Miao Sun; Min Li (Wolters Kluwer Health, 2021)
Abstract. Introduction:. Muir-Torre syndrome is a phenotypic variant of Lynch syndrome characterized by a predisposition for the development of visceral malignant disease and sebaceous gland neoplasms, and it is caused by germline mutations in the mismatch repair genes MSH2 and MLH1. Here, we reported a patient with sebaceous neoplasm containing MLH1 c.199G>A mutation. Case presentation:. The proband was a 42-year-old man who had undergone surgical resection of colorectal adenocarcinoma at 28 years. He presented with macular rashes and red papule. Histological examination of the lesion on his head revealed a sebaceoma at 37 years. Follow-up of the family history revealed that the proband's 65-year-old mother had been highly suspected to have Lynch syndrome with colorectal cancer at 40 years of age. The proband's daughter underwent colonoscopy because of blood in the stool at the age of 13 years, but no abnormalities were found. Discussion:. We have herein reported a pathogenic missense mutation c.199G>A (p.Gly67Arg) in exon 2 of MLH1 in patients with MTS. This mutation has been reported in patients with Lynch syndrome who have no skin tumors. However, we also found that some patients with MTS had no history of any internal malignancy or skin tumor. Our data support the idea that a hiatus of many years may pass before both elements-a sebaceous neoplasm and an internal cancer-are present in a patient, thus finally allowing the diagnosis of MTS. Conclusion:. A pathogenic Lynch syndrome mutation c.199G>A in exon 2 of the MLH1 gene was found in a patient with MTS who presented with a sebaceous neoplasm.